No Effect of Dietary Aspartame or Stevia on Pancreatic Acinar Carcinoma Development, Growth, or Induced Mortality in a Murine Model - Dooley, James; Lagou, Vasiliki; Dresselaers, Tom; van Dongen, Katinka A.; Himmelreich, Uwe; Liston, Adrian (Frontiers in Oncology, 2017)
Pancreatic cancer has an extremely poor prognosis, largely due to a poor record for early detection. Known risk factors for pancreatic cancer include obesity, diet and diabetes, implicating glucose consumption and regulation as a key player. The role of artificial sweeteners may therefore be pertinent to disease kinetics. The oncogenic impact of artificial sweeteners is a highly controversial area. Aspartame, one of the most studied food additives, is widely recognized as being generally safe, although there are still specific areas where research is incomplete due to study limitations. Stevia, by contrast, has been the subject of relatively few studies, and the potential health benefits are based on extrapolation rather than direct testing. Here we used longitudinal tracking of pancreatic acinar carcinoma development, growth and lethality in a sensitized mouse model. Despite exposure to aspartame and stevia from the in utero stage onwards, we found no disease modification activity, in either direction. These results contribute to the data on aspartame and stevia safety, while also reducing confidence in several of the purported health benefits.